Stable Isotope Labeling with Amino Acids in Cell Culture (SILAC)-Based Strategy for Proteome-Wide Thermodynamic Analysis of Protein-Ligand Binding Interactions - Tran, Duc T. (The American Society for Biochemistry and Molecular Biology, 2014)
Described here is a quantitative mass spectrometry-based proteomics method for the large-scale thermodynamic analysis of protein-ligand binding interactions. The methodology utilizes a chemical modification strategy termed, Stability of Proteins from Rates of Oxidation (SPROX), in combination with a Stable Isotope Labeling with Amino Acids in Cell Culture (SILAC) approach to compare the equilibrium folding/unfolding properties of proteins in the absence and presence of target ligands. The method, which is general with respect to ligand, measures the ligand-induced changes in protein stability associated with protein-ligand binding. The methodology is demonstrated in a proof-of-principle study in which the well-characterized protein-drug interaction between cyclosporine A (CsA) and cyclophilin A was successfully analyzed in the context of a yeast cell lysate. A control experiment was also performed to assess the method's false positive rate of ligand discovery, which was found to be on the order of 0.4 - 3.5%. The new method was utilized to characterize the adenosine triphosphate (ATP)-interactome in Saccharomyces cerevisiae using the nonhydrolyzable ATP analog, adenylyl imidodiphosphate (AMP-PNP), and the proteins in a yeast cell lysate. The new methodology enabled the interrogation of 526 yeast proteins for interactions with ATP using 2035 peptide probes. Ultimately, 325 peptide hits from 139 different proteins were identified. Approximately 70% of the hit proteins identified in this work were not previously annotated as ATP binding proteins. However, nearly two-thirds of the newly discovered ATP interacting proteins have known interactions with other nucleotides and co-factors (e.g. NAD and GTP), DNA, and RNA based on GO-term analyses. The current work is the first proteome-wide profile of the yeast ATP-interactome, and it is the largest proteome-wide profile of any ATP-interactome generated, to date, using an energetics-based method. The data is available via ProteomeXchange with identifiers PXD000858, DOI 10.6019/PXD000858, and PXD000860.